Sixteen-years Application of Organic Manures and Fertilizers in Pearl Millet–Wheat Cropping System on Soil Fertility and Soil Carbon Management Index in an Inceptisol of Subtropical India - B.H. Kumara (Journal of the Indian Society of Soil Science, 2022)
A study was undertaken in a long-term experiment on effect of organic manures and nutrient managementon soil fertility and soil organic carbon (SOC) after 16 years cycles of pearl millet–wheat cropping systemin a coarse loamy, Typic Haplusterts of subtropical India. Significant build-up of soil fertility in terms ofalkaline KMnO4-N, Olsen-P, NH4OAc-K as well as SOC namely, total organic carbon (TOC), Walkley andBlack organic carbon (WBC), labile organic carbon (LBC) and periodical changes of SOC during croppingseason were maintained under different organic manures (FYM, poultry manure and pressmud) alone orintegrated nutrient management over control plot in different depths (0-15, 15-30 and 30-45 cm) of thesoils. The highest values of TOC (13.2 g kg-1), WBC (11.2 g kg-1) and LBC (1.22 g kg-1) were maintainedin 15 t FYM + 150 kg N ha-1 + 30 kg P2O5 ha-1 treated plot. The magnitude of change in WBC in subsurface(15–30 and 30-45 cm) soil was low compared to surface soil (0-15 cm). Highly strong relationshipswere exhibited between LBC with yield, indicating that these pools are more important for nutrient turnoverand their availability to plants than total SOC. Carbon management index revealed that integratednutrient management could be followed for enhancement of crop productivity, nutrient availability and soilcarbon pools for long-term. These results conclude that for sustainable crop production and maintainingsoil quality, input of organic manure like FYM is of major importance and should be advocated in thenutrient management of intensive cropping system for improving soil fertility and biological properties ofsoils.